The Potential of Metabolomic Analyses as Predictive Biomarkers of Preterm Delivery: A Systematic Review - Ronde, Emma; Reiss, Irwin K. M.; Hankemeier, Thomas; De Meij, Tim G.; Frerichs, Nina; Schoenmakers, Sam (Frontiers in Endocrinology, 2021)
Scope: as the leading cause of perinatal mortality and morbidity worldwide, the impact of premature delivery is undisputable. Thus far, non-invasive, cost-efficient and accurate biochemical markers to predict preterm delivery are scarce. The aim of this systematic review is to investigate the potential of non-invasive metabolomic biomarkers for the prediction of preterm delivery. Methods and results: Databases were systematically searched from March 2019 up to May 2020 resulting in 4062 articles, of which 45 were retrieved for full-text assessment. The resulting metabolites used for further analyses, such as ferritin, prostaglandin and different vitamins were obtained from different human anatomical compartments or sources (vaginal fluid, serum, urine and umbilical cord) and compared between groups of women with preterm and term delivery. None of the reported metabolites showed uniform results, however, a combination of metabolomic biomarkers may have potential to predict preterm delivery and need to be evaluated in future studies.